Molecular characterization of Wnt pathway and function of β-catenin overexpression in medulloblastoma cell lines - Geron, Lenisa (Cytotechnology, 2018)
Medulloblastoma (MB) is the most common malignant childhood brain tumor. MB is currently classified into four molecular subgroups (Wnt, Shh, Group 3, and Group 4). The wingless (Wnt) pathway is responsible for embryonic development and is deregulated in MB. We analyzed the activation of the Wnt pathway in MB cell lines and its correlation with the Shh pathway, with emphasis on the importance of cellular characterization. Transient β-catenin transfection led to an increase in the β-catenin gene and protein expression in MB cell lines. Wnt pathway activation resulted in a reduced number of colonies in all cell lines studied and a significant increase in the G2/M cell cycle phase only in ONS-76 cells. Regarding the Shh pathway, transfection caused a reduced expression of the PTCH1 and SMO genes only in the UW473 cells. Further studies are needed to understand the mechanism underlying the molecular events associated with the effects of Wnt activation in MB.